Incidental finding of accessory mitral valve tissue on routine adult echocardiography. Issue 8 (1st March 2021) - Theodoropoulos, Konstantinos C.; Avci Demir, Fulya; Masoero, Giovani; Lukban, Benito Francisco; Fonseca, Tiago; Monaghan, Mark J.; Papachristidis, Alexandros
Abstract: Accessory mitral valve tissue is a rare congenital cardiac abnormality that sometimes can cause left ventricular outflow tract obstruction. We herein present the case of a 55‐year‐old male with an incidental finding of accessory mitral valve tissue on transthoracic echocardiography. The patient was managed conservatively as accessory tissue was not causing left ventricular outflow obstruction and there were no hemodynamic consequences.